(untitled) (Research, Society and Development, 2019)
The present study aimed an understanding by a bibliographic review, know how to constitute psychically or perverse subject from familiar relations using the psychoanalytic theory. The analyzed data pointed out that problems or failures in the performance of maternal function, that is, a process of attachment of the process of mother-infant bonding, a non-favorable family environment with dysfunctional relationships can negatively repercussions without the child’s psychic development, potentiating affective disorders and consequently contribute to a constitution of the perverse subject.